2012
DOI: 10.1002/mrc.3812
|View full text |Cite
|
Sign up to set email alerts
|

Combined experimental–theoretical NMR study on 2,5‐bis(5‐aryl‐3‐hexylthiophen‐2‐yl)‐thiazolo[5,4‐d]thiazole derivatives for printable electronics

Abstract: Four 2,5-bis(5-aryl-3-hexylthiophen-2-yl)thiazolo[5,4-d]thiazole derivatives have been synthesized and thoroughly characterized. The extended aromatic core of the molecules was designed to enhance the charge transport characteristics, and solubilizing hexyl side chains were introduced on the thiophene subunits to enable possible integration of these semiconducting small molecules in printable electronics. Complete elucidation of the chemical structures by detailed one-dimensional/two-dimensional NMR spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…A series of highly soluble functionalized 2,5-dithienylthiazolo [5,4-d]thiazoles (DTTzTz) was recently synthesized within one of our groups and these expanded semiconductors were investigated as active materials for solution-processable OFETs. [9][10][11] In the OPV field, a number of low bandgap copolymer structures incorporating TzTz moieties as the electron poor units have very recently appeared in the literature, showing rather high charge-carrier mobilities and power conversion efficiencies. 12,13 At present the most successful organic solar cells are based on the 3-dimensional bulk heterojunction (3D BHJ) approach in which the active layer consists of two interpenetrating networks of an electron donor compound, most often a conjugated polymer, and an electron acceptor, in many cases fullerene derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…A series of highly soluble functionalized 2,5-dithienylthiazolo [5,4-d]thiazoles (DTTzTz) was recently synthesized within one of our groups and these expanded semiconductors were investigated as active materials for solution-processable OFETs. [9][10][11] In the OPV field, a number of low bandgap copolymer structures incorporating TzTz moieties as the electron poor units have very recently appeared in the literature, showing rather high charge-carrier mobilities and power conversion efficiencies. 12,13 At present the most successful organic solar cells are based on the 3-dimensional bulk heterojunction (3D BHJ) approach in which the active layer consists of two interpenetrating networks of an electron donor compound, most often a conjugated polymer, and an electron acceptor, in many cases fullerene derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…14 DFT calculations revealed that the principal g values depend not only on the nature of the DTTzTz substituents, but are also slightly influenced by the conformer structure. The heterogeneity due to the predicted coexistence of different conformers 12 is not resolved in the experimental spectra, and if present only contributes to the EPR linewidth. Although two EPR signals were found to contribute to the high-field EPR spectra of oxidized Th-DTTzTz (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…The synthesis of 2,5-bis(4-hexyl-2,2 0 -bithiophene-5-yl)thiazolo [5,4-d]thiazole (Th-DTTzTz) and 4,4 0 -[5,5 0 -(thiazolo [5,4-d]thiazole-2,5-diyl)bis(4-hexylthiophene-5,2-diyl)]dibenzonitrile (4-CN-Ph-DTTzTz) has been reported elsewhere. [11][12][13] MDMO-PPV was obtained from Covion (M w = 716 kg mol À1 , PD = 6.5). Solutions were prepared in chloroform (CHCl 3 , Acros Organics, 99.9%).…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations